Effects of smoking cessation on the outcomes of non‐surgical periodontal therapy: a systematic review and individual patient data meta‐analysis. (16th April 2013) - Chambrone, Leandro; Preshaw, Philip M.; Rosa, Ecinele Francisca; Heasman, Peter A.; Romito, Giuseppe A.; Pannuti, Claudio Mendes; Tu, Yu‐Kang
Abstract Aim To conduct an individual patient data (IPD) meta‐analysis to assess the effect of smoking cessation (SC) on clinical outcomes following the non‐surgical periodontal treatment in patients with chronic periodontitis. Methods MEDLINE, EMBASE and CENTRAL were searched up to, and including, August 2012. Prospective cohort studies of at least 6 months' duration were included if the participants met the following criteria: (1) smokers who had expressed an interest in quitting the habit; and (2) a diagnosis of periodontitis. Search was conducted by two independent reviewers. IPD meta‐analyses were undertaken using multiple linear or Poisson regression to evaluate the impact of SC on five different dependent variables. Results Of 2455 potentially eligible articles, two studies were included. The two studies found that SC seems to promote additional beneficial effects in reducing probing depths (PD) and improving attachment level following non‐surgical periodontal treatment. The IPD approach allowed data combination but it might not have usefully added strength to the data in this review. Conclusion SC seems to be an important component of periodontal therapy, and smokers should be encouraged to quit as part of their overall periodontal management; however, only a limited base of evidence was available for analysis.